Pengembangan Modul Konseling Keluarga dengan Teknik Positive Reinforcement untuk Meningkatkan Kepercayaan Diri Siswa - Inggita Al-Syauqina Puspitasari; Dwi Sona; Yasintha Sari Pratiwi; Muhaimin Abdillah (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This research is motivated by the results of student needs assessments through AKPD, AUM, observations, and interviews that indicate that there are students with low levels of self-confidence caused by the lack of role and support from the family. One effort that can be done to overcome this problem is to develop service media that involve the role of the family. Therefore, this study aims to develop a family counseling module with positive reinforcement techniques to increase student self-confidence. This study uses the Research and Development (R&D) Level 1 method, which focuses on product design and validation without extensive field trials. The product developed is a family counseling module with positive reinforcement techniques to increase student self-confidence. Validation was carried out by three validators consisting of material experts, linguists, and guidance and counseling practitioners. The assessment uses a validation sheet with a Likert scale of 1-4 on the aspects of material, language, and practicality, then the percentage of feasibility is calculated: ≤40% = less, 41-60% = sufficient, 61-80% = feasible, and 81-100% = very feasible. The results showed that the validation score from subject matter experts was 87.5%, from language experts 97.5%, and from guidance and counseling practitioners 100%, resulting in an average module feasibility percentage of 95%. These results indicate that this module is categorized as "very feasible" for use as a family counseling service in schools. However, because this study used a Level 1 R&D approach, the module was only tested for feasibility and validity. Therefore, this study did not test the module's effectiveness or its impact on increasing participants' self-confidence.